1991
DOI: 10.1007/bf01313094
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rates of midwater crustaceans as a function of depth of occurrence off the Hawaiian Islands: Food availability as a selective factor?

Abstract: During July of 1983, 1986, we measured rates of oxygen consumption of 234 individuals of 17 species of midwater crustaceans (orders Decapoda, Mysidacea, and Euphausiacea) off the Hawaiian islands at depths from the surface to greater than 1200 m. The routine metabolic rates declined with increasing depths of the species' occurrence to an extent greater than could be accounted for by depth-related changes in body size or water temperature. Most species appeared able to regulate their oxygen consumption down to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…According to the visual interactions hypothesis, this loss of visual ability decreases selection for locomotory abilities. Investigations on the locomotory abilities of the bathypelagic mysid Gnathophausia ingens have shown that its locomotor abilities are reduced compared to shallower living crustaceans (Cowles and Childress 1988). We predict that comparative studies on chaetognath locomotion will not find any decrease in the locomotor abilities of bathypelagic species; many deeper living species are in fact more robust than their shallower counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…According to the visual interactions hypothesis, this loss of visual ability decreases selection for locomotory abilities. Investigations on the locomotory abilities of the bathypelagic mysid Gnathophausia ingens have shown that its locomotor abilities are reduced compared to shallower living crustaceans (Cowles and Childress 1988). We predict that comparative studies on chaetognath locomotion will not find any decrease in the locomotor abilities of bathypelagic species; many deeper living species are in fact more robust than their shallower counterparts.…”
Section: Discussionmentioning
confidence: 94%
“…However, recent hypotheses have indicated that adaptation to low levels of light in mid-depth environments could account for this decline of biological processes, and in particular for the metabolic rates of midwater animals (Childress 1995). The metabolism of midwater fishes, crustaceans and cephalopods decreases down to 1000 m depth and below this depth the metabolism ceases to decline (Childress & Somero 1979, Cowles et al 1991, Seibel et al 2000. These authors postulate that light plays an important role not only in the distribution of species but also in the evolutionary processes of these midwater animals.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced metabolism may be considered an adapted characteristic of deeper-living species (cf. Childress 1971, 1975, Torres et al 1979, Torres & Somero 1988, Cowles et al 1991.…”
Section: Respiration and Depthmentioning
confidence: 99%
“…Two of the studies took place in the sub-Arctic transitional waters of the California borderland (Childress 1975, Quetin et al 1980, one in the subtropical waters of the Gulf of Mexico ), 1 in the subtropical waters of the Pacific central gyre near Hawaii (Cowles et al 1991), and 2 in the polar waters of the Antarctic (Ikeda 1988, this paper). The taxonomic composition and life habits of the micronektonic Crustacea examined differ considerably between studies, mirroring the composition of the local fauna.…”
Section: Comparison With Other Systemsmentioning
confidence: 99%